👤

wyrażenie [tex]\sqrt[3]{4} * \sqrt[5]{8} * 2 ^{-1}[/tex] zapisane w postaci potęgi liczby 2 jest równe

Odpowiedź :

[tex]\sqrt[3]{4}\cdot\sqrt[5]{8}\cdot2^{-1}=4^{\frac13}\cdot8^{\frac15}\cdot2^{-1}=\\\\=(2^2)^{\frac13}\cdot(2^3)^{\frac15}\cdot2^{-1}=2^{\frac23}\cdot2^{\frac35}\cdot2^{-1}=\\\\=2^{\frac23+\frac35+(-1)}=2^{\frac{10}{15}+\frac9{15}-1}=2^{\frac{19}{15}-1}=2^{\frac4{15}[/tex]

skorzystaliśmy ze wzorów:

[tex]\sqrt[n]{a}=a^{\frac1{n}} \\\\(a^n)^m=a^{n\cdot\ m}\\\\a^n\cdot\ a^m=a^{n+m}[/tex]